Personal pronouns as guiding strategies in academic lectures across two institutions - Noor Mala Ibrahim; Ummul K. Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Studies on linguistic features employed by native-speaker (NS) and non-native speaker (NNS) lecturers when delivering academic lectures have been scarce, perhaps due to the difficulty and complexity of collecting data for analysis. This paper attempts to fill the gap by analyzing how personal pronouns I, you and we are used in undergraduate engineering lectures in two instructions across different backgrounds to emphasize the way lecturers guide their students throughout the unfolding texts. Ten lectures (five each from a Malaysian university and a British university) covering fundamental engineering courses attended by second-year Civil Engineering students delivered by different lecturers were video-recorded, transcribed, and analyzed. Based on eleven discourse functions that could facilitate students’ understanding of lecture contents, pronouns I, you and we that occurred in phrases and clauses that manifest the identified lecture discourse functions were analyzed and compared. Findings reveal apparent similarities in the use of pronouns by NS and NNS lecturers in guiding students to follow their lectures. You and we have been identified as the most common pronouns used by both NS and NNS lecturers among the three pronouns. The findings reveal that factors that underline lectures as a genre override all others in the lecturer’s delivery as far as pronouns are concerned. The findings are nevertheless valuable for training young lecturers to improve delivery efficiency, especially for academic mobility for both students and lecturers.